Lhia: Um Agente Conversacional Inteligente para Educação em Aleitamento Materno e Recrutamento de Mães Doadoras - CORREA, Joeckson dos Santos (2023)
Breast milk is the most important way to feed and protect newborns, as it has the components to ensure human health. The Human Milk Banks (HMB) form a network that takes essential services to ensure that newborns and mothers can enjoy the benefits of breast milk. Despite this, there is low adherence to exclusive breastfeeding in Brazil, and human milk stocks available in HMBs are usually below demand. The objective of this work is to co-develop a smart conversational agent for breastfeeding education and human milk donor recruitment for HMBs. The co-development methodology Conversation-Drive Development will be conducted in partnership with health professionals from the HMB of the University Hospital of UFMA. The chatbot will work as a communication and information technology in breastfeeding education for mothers. It is expected that maternal perception, knowledge and attitude will be improved, and thus the prevalence rate of exclusive breastfeeding will increase, in addition to the increase in the number of donors.